Data Mining and its Techniques (International Journal of Engineering and Computer Science, 2017)
With the evolution of technology, the speed at which we gather data has increased exponentially. The aim of organizing and providing meaningful access to data is the task of of prime importance. We can see a tremendous potential in it as the influx of data brings with it an exponential growth in knowledge. The process through which all the data is traversed and meaningful patterns discovered is known as Data Mining or Knowledge Discovery. This review provides an insight into the most common techniques in the field such as Prediction, Clustering, Association, Sequential Pattern detection etc.